Synergic photocatalytic effects of nitrogen and niobium co-doping in TiO2 for the redox conversion of aquatic pollutants under visible light - Lim, Jonghun; Murugan, Palanichamy; Lakshminarasimhan, Narayanan; Kim, Jae Young; Lee, Jae Sung; Lee, Sang-Hyup; Choi, Wonyong (ACADEMIC PRESS INC ELSEVIER SCIENCE, 2014)
Nitrogen and niobium co-doped TiO2 was synthesized by a simple sol-gel method and its visible light photocatalytic activities were compared with bare, N-, and Nb-doped TiO2. The synthesized photocatalysts were characterized by powder X-ray diffraction (XRD), diffuse reflectance UV-Visible absorption spectroscopy, FT-IR spectroscopy, X-ray photoelectron spectroscopy, and energy-dispersive X-ray analysis. TiO2 co-doped with N and Nb can have unique properties distinguished from the singly doped TiO2 in the aspects of the dopant-induced charge distribution, vacancy sites, structural stability, defect energy levels, and optical absorption. The most notable is that the visible light absorption by (N,Nb)-TiO2 was significantly higher than either of N- or Nb-TiO2 sample. The doped samples exhibited a slight change in the band gap (by similar to 0.1 eV) compared with bare TiO2, which could be confirmed by Tauc plot, MottSchottky plot, and the electronic structure calculation. The co-doping of N and Nb in TiO2 induced the creation of the mid-gap levels and Ti3+ states that enhance the visible light absorption. The photocatalytic activities of bare, N-, Nb-, and (N,Nb)-TiO2 were compared for the photocatalytic degradation of 4-chlorophenol (4-CP), oxidation of iodide, and reduction of chromate (Cr-VI) in the aqueous phase under visible light (lambda >420 nm). For all tested substrates, (N,Nb)-TiO2 exhibited the markedly higher activities than either N-TiO2 or Nb-TiO2. A similar trend was also observed for the photocurrent generation under visible light irradiation. (C) 2013 Elsevier Inc. All rights reserved.
Keywords: NB-DOPED TIO2; SENSITIZED SOLAR-CELLS; THIN-FILMS; ELECTRONIC-STRUCTURE; METHYLENE-BLUE; SURFACE; TITANIA; PERFORMANCE; NANOPARTICLES; DEGRADATION